2017
DOI: 10.1089/thy.2016.0210
|View full text |Cite
|
Sign up to set email alerts
|

Thyroglobulin Liquid Chromatography–Tandem Mass Spectrometry Has a Low Sensitivity for Detecting Structural Disease in Patients with Antithyroglobulin Antibodies

Abstract: Background: Thyroglobulin (Tg) measurement in patients with positive antithyroglobulin antibodies (antiTgAbs) is not reliable. Tg measurement using liquid chromatography-tandem mass spectrometry (LC/MS) may be useful in this setting. Methods: This is a retrospective study with the objective of determining the accuracy of Tg-LC/MS in patients with thyroid cancer with anti-TgAbs. All patients with follicular cell-derived thyroid cancer (TC) who had thyroglobulin measured using LC/MS assay from November 1, 2013, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 20 publications
2
16
0
1
Order By: Relevance
“…We have recently reported that the rise in TgAb IgG observed after 131 I treatment for Graves' hyperthyroidism is restricted to IgG1 and IgG3 (29). The present findings, in addition to previous data, support the concept that, in patients with TgAb, the lower than expected Tg concentrations observed when Tg is measured by IMA and tandem mass spectroscopy (2,6,8,9,27) is mainly due to a truly low This paper has been peer-reviewed and accepted for publication, but has yet to undergo copyediting and proof correction. The final published version may differ from this proof.…”
Section: Discussionsupporting
confidence: 87%
“…We have recently reported that the rise in TgAb IgG observed after 131 I treatment for Graves' hyperthyroidism is restricted to IgG1 and IgG3 (29). The present findings, in addition to previous data, support the concept that, in patients with TgAb, the lower than expected Tg concentrations observed when Tg is measured by IMA and tandem mass spectroscopy (2,6,8,9,27) is mainly due to a truly low This paper has been peer-reviewed and accepted for publication, but has yet to undergo copyediting and proof correction. The final published version may differ from this proof.…”
Section: Discussionsupporting
confidence: 87%
“…The presence of specific somatic tumor mutations has been integrated into the ATA risk stratification classification (9). Although the presence of BRAFV600E mutation has been associated with higher recurrence rates in tumors of >1 cm (53) that are considered as at intermediate risk of recurrence, this is not true for intrathyroidal microPTCs (54).…”
Section: Low Risk Tumors Represent the Majority Of Dtcmentioning
confidence: 99%
“…Novel biomarkers are emerging as replacements for serum Tg in these difficult cases, such as circulating microRNAs and other nucleic acids, but still need to be standardized and clinically validated 42 44 . The use of mass spectrometry for measuring serum Tg levels in the presence of TgAb also needs to be validated 45 , 46 . Sensitive Tg assays that can detect serum concentrations as low as 0.1 ng/mL are currently used and provide similar information on disease status as rhTSH-stimulated Tg obtained in the past with assays that had a sensitivity of 1 ng/mL.…”
Section: Follow-up Toolsmentioning
confidence: 99%